Frequency of Preeclampsia in Obese Woman Presenting at Civil Hospital Karachi - Jahooran Mariyah Bibi Goolamnobee, Gulfishan Haq, Sadaf Sabir, Saima Shaikh, Sheik Mamode Adeel Auckloo, Nusrat Shah, (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: To determine the frequency of preeclampsia in obese women at civil hospital Karachi. Methods: A total 126 patients from March-2020 up to December-2021 were inducted in the study with non-probability consecutive sampling. Women of 18-40 years of age having singleton pregnancy with obesity with gestational age ≥ 20 weeks were included after informed consent. Blood pressure (BP) was measured after 20 weeks of gestation. Urine for protein was checked if BP was found to be ≥140/90 mmHg for diagnosis of pre-eclampsia. Result: The women had a mean age of 28.56 ± 3.848 years. Age at presentation was highest in the group 25-31 years which represented 87 (69.04%). 23.02% of the women were nulliparous, 76.98% were multiparous. The mean ± SD gestational age was 34.52 ± 3.775 and 72 (57.1%) were in their 35-40 weeks of gestation. 91 women representing 72.2% had a BMI of 30-33 kg/m2. Pre-eclampsia was diagnosed in 33 (26.2%) obese patients (Table 2). Conclusion: The frequency of 26.2% of Pre-eclampsia in obese women is significantly high. Women should be counseled before conception to decrease their BMI.